Comparison between histochemical and immunohistochemical methods for diagnosis of sporotrichosis. - Marques, M E (1992)
AIMS: To compare the efficacy of histochemical and immunohistochemical methods in detecting forms of Sporothrix schenckii in tissue. METHODS: Thirty five cutaneous biopsy specimens from 27 patients with sporotrichosis were stained by histochemical haematoxylin and eosin, periodic acid Schiff, and Gomori's methenamine silver methods and an immunohistochemical (avidin-biotin complex immunoperoxidase) (ABC) technique associated with a newly produced rabbit polyclonal antibody anti-Sporothrix schenckii. RESULTS: A total of 29 (83%) cases were positive by the ABC method used in association with anti-Sporothrix schenckii rabbit polyclonal antibodies. Histochemical methods, using silver staining, periodic acid Schiff, and conventional haematoxylin and eosin detected 37%, 23%, and 23% of forms of S schenckii, respectively. The ABC technique was significantly more reliable than periodic acid Schiff and silver staining techniques. CONCLUSIONS: It is concluded that immunostaining is an easy and rapid method which can efficiently increase the accuracy of the diagnosis of sporotrichosis in human tissue.